Ormond Beach Native Plant Restoration - McCormick, Tom; Buckley, Lorraine (Oxnard College)
Oxnard College Environmental Studies project will have students focus restoring native plants under the direction of Dr. Lorraine Buckley and Tom McCormick. The restoration program will control non-native plants thus improving the quality function, and diversity of the dune ecosystem at Ormond Beach.